Prekariat i niepełnosprawność – o tymczasowości i niepewności edukacji, rehabilitacji, pracy i życia - Wlazło, Marcin (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The article concerns the links between precarity and disability as the social phenomenons connected with the theoretical problems of exclusion and laws marginality as well as the wider context of the existencial temporariness and uncertainty. There is a clear semantic identity between precarity and disability. The verb to care is the root of the English word precarity and the noun care is present in Polish phrase child of special care which means exactly the same as child with special needs or child with disability. There were given the examples of positive realization of normalization of people with disabilities in the conditions of the neoliberal economy.